The Role of Pancasila and Citizenship Education in the Multicultural Life of Students in Schools - Mohammad Deva Setyawan; Ratna Sari Dewi; Febrian Alwan Bahrudin (Universitas Pendidikan Ganesha, 2024)
The vast diversity that exists in Indonesia, aside from being a valuable national asset, can also become a trigger for conflict. Many conflicts and disputes arise due to differences in background, such as ethnicity, race, religion, and others. This study aims to explore the extent to which Pancasila Education can contribute to multicultural life in schools and to analyze how far it can shape and instill multicultural values that embrace diversity within the school environment. The findings of this study were obtained through interviews, observations, and documentation involving research subjects including Pancasila Education teachers, the Vice Principal for Student Affairs, and students. The collected data were then analyzed. The results indicate that Pancasila Education plays a significant role in the multicultural lives of students at school. Students believe that Pancasila Education provides them with a deeper understanding of multicultural values such as tolerance, democracy, justice, and equality. Pancasila Education is vital in fostering multiculturalism among high school students because it is fundamentally a subject that emphasizes character, values, and morals. It not only teaches theoretical concepts but also stresses the importance of applying those concepts in daily life. This research is beneficial for various stakeholders to understand and strengthen multiculturalism, especially in schools, by promoting attitudes such as tolerance, democracy, justice, and equality, which are essential for building and maintaining harmony and unity within the school community.